Alteration of gut microbiota composition and function of Indian major carp, rohu (Labeo rohita) infected with Argulus siamensis. (March 2022) - Mondal, Hemanta Kumar; Maji, Usha Jyoti; Mohanty, Sriprakash; Sahoo, Pramoda Kumar; Maiti, Nikhil Kumar
Abstract: Gut microbiome homeostasis is critical in preventing diseases. However, the effect of disease on gut microbiota assembly remains unclear. At present, there are no reports on the composition and functional analysis of intestinal microbiota of Indian major carp, rohu ( L. rohita) infected with ectoparasite, Argulus. In this study, we analysed and compared the intestinal microbiota of healthy and Argulus- infected rohu by 16S rRNA amplicon sequencing. Argulus infection could significantly influence the diversity and richness of the gut microbiota. However, abundance of Actinobacteria and Patescibacteria were enriched significantly in Argulus- infected fish. Venn diagram revealed that there were many more unique genera in the infected group as compared to control fish. The genera, Stenotrophomonas and Pirellula were significantly increased in infected fish while the abundance of Reyranella was decreased. LEfSe analysis showed a significant enrichment in abundances of 11 taxa in healthy group and 17 taxa in infected group. Furthermore, genera Rubellimicrobium, Dielma, Hyphomicrobium, Reyranella, Streptomyces and Cloacibacterium performed the best in differentiating between both the groups. Predicted microbiota function by PICRUSt revealed that the gut microbiota of infected fish was mainly associated with enriched synthesis of chitinases, chitin binding proteins, osmoprotectant proteins and sulfatases enzymes. There was a positive association between the structural and functional composition of the gut microbiota. The results indicated that the Argulus infection could affect the intestinal microbiota composition and function of rohu . Highlights: Effect of Argulus infection on gut microbiota of rohu ( Labeo rohita ) was analysed. Argulus infection did not significantly affect the diversity of rohu gut microbiota. Stenotrophomonas and Pirellula were significantly increased in infected fish. Dielma, Hyphomicrobium and Rubellimicrobium were gut biomarkers in infected group. Chitinase, osmoprotectant and sulfatase synthesis genes were enriched in infected fish.